Salat Subuh Berjama’ah Pengaruhnya Terhadap Kedisiplinan Peserta Didik - Nurmala; Indry Nirma Yunizul Pesha; Rusdi Kasman (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Morning prayers in congregation have an important role in the discipline of students at SMA Dwiwarna Boarding School, Parung Bogor Regency. Morning prayers in congregation have very special advantages. Praying in congregation will get a reward that is 27 degrees superior to praying alone. The discipline of morning prayers plays a very important role in trying to encourage students to be more obedient and comply with existing rules at school, especially congregational morning prayers. Prayer is the second pillar of religion after the shahada. Prayer is a pillar of the Islamic religion, prayer makes life calmer and always grateful, prayer is also a form of devotion to Allah SWT. The aim of the research is to solve the problem that will be carried out by the researcher which is taken through the title congregational morning prayer and its influence on the discipline of students at Sma Dwiwarna Boarding School, Parung District, Bogor, where teachers and dormitory supervisors have a very important role for students in the school. guide and advise to achieve the desired goals. This research aims to measure the habit of morning prayers in congregation on students' discipline to find out how influential the morning prayers are in discipline. The discussion of this research is seen from a framework of thinking which aims to find mature concepts that are used to explain each problem in the research, including, congregational morning prayers, terms and conditions for prayer, easy ways to wake up at dawn and how to find the virtues of morning prayers, in The variable is explained by discipline, factors and morals in discipline. The research method used is a survey method with a quantitative approach. Data is collected through questionnaires/questionnaires from students, as well as documentation as concrete evidence in research. It is hoped that the results of this research will provide an overview of the extent to which the habit of congregational morning prayers affects students' discipline and can be applied not only in the school environment.